Formulation of Selection Indices for Yield Enhancement in Bread Wheat (Triticum aestivum L.): SELECTION INDICES FOR YIELD ENHANCEMENT IN WHEAT - Himalay Patel; Urvashi C. Mangroliya; Nikunj A. Parmar (Annals of Arid Zone, 2024)
The present experiment was designed with the objective of creating selection indices within 50 different genetic varieties of bread wheat (Triticum aestivum L.) using the discriminant-function technique under timely sown conditions. We developed a total of thirty-one selection indices, which incorporated grain yield plant-1 and four other yield components. By including a greater number of characteristics within the index, the effectiveness of the selection process was enhanced. The selection index, primarily focused on two traits, namely biological yield plant-1 and harvest index, emerged as the most efficient for identifying higher-yielding strains. The findings underscored the importance of assigning maximum priority to these attributes when making selections related to yield traits in bread wheat.